Cassava, plantain and moringa grown in an Alfisol and their resilience to bush fire in eastern Nigeria - Asadu, C.L.A.; Unagwu, B.O.; Dixon, A.; Okechukwu, R.; Ilona, Paul; Asadu, A.N. (2019)
Research on the resistance of cassava to fire is scarce because ordinarily researchers would not set their cassava farms on fire for such evaluation. Stems rendered useless by fire were commonly reported by farmers but no information on root yields and shoot regeneration. This study compared the superiority of two improved International Institute of Tropical Agriculture (IITA) cassava varieties (“Yellow root” and “Agric”) over plantain and moringa in a cassava + plantain + moringa intercropping arranged in a randomized complete block design at the University of Nigeria, Nsukka, Research Farm. The original aim was to compare the performances of the crops in the mixture. It was set on fire by unknown persons in early February 2018. Crop growth data were collected after six months. Less than 5% and 4% of plantain and moringa stands regenerated respectively. The stands appeared impoverished. More than 90% of both cassava varieties regenerated stems suitable for use as cuttings. Average fresh root yield obtained was 18.5 t ha-1 with ˜ 95% marketable and only < 5% rotten. The “Yellow root” gave significantly higher starch content (30.9 vs 19.7%) than “Agric”. The root: shoot ratio (3.35 vs 5.28), fresh root weight (22.5 vs 14.5 t h1) and marketable root weight (21.61 vs 13.72 t ha1) for both varieties were statistically similar. This evaluation confirmed cassava as a better food security crop than plantain and more resilient to fire than both plantain and moringa. The two IITA improved varieties proved to be equally resilient to bush fire.